Work-Family Conflict of Emergency Nurses and Its Related Factors: A National Cross-Sectional Survey in China - Wu, Yafei; Zhou, Xuan; Gong, Yanhong; Jiang, Nan; Tian, Mengge; Zhang, Jiali; Yin, Xiaoxv; Lv, Chuanzhu (Frontiers in Public Health, 2021)
The prevalence of work-family conflict (WFC) among nurses was high, especially in the emergency department. WFC has a series of negative influences on emergency nurses, but factors associated with WFC require elucidation. Thus, we conducted a national cross-sectional survey among emergency nurses in China. In this study, we described the current situation of WFC and explored its related factors among emergency nurses in China. We found that the WFC of emergency nurses was severe, and emergency nurses aged 25 to 34, male, married, highly educated, with high professional title and long years of service, perceiving the shortage of nurses, experiencing a high frequency of night shift, tended to have higher WFC. Targeted interventions, such as reasonable work allocation, adequate staffing, and a scientific night shift system should be implemented to alleviate the WFC of emergency nurses.